Studies on Homalomeneae (Araceae) of Borneo XII — Homalomena tirtae, a new species from Kalimantan Timur, Indonesian Borneo, and notes on the Homalomena Borneensis Complex - Ni Putu, Sri Asih; Agung, Kurniawan; Boyce, P.C (BGBM Berlin-Dahlem., 2012)
Homalomena tirtae from Mount Sidi, Kalimantan Timur, is described as a species new to science and illustrated from living plants. It is the fourth described species of the Borneensis Complex and the first recorded for eastern Borneo. A key to and a comparison plate with the spadices of the four species of the Borneensis Complex is provided.